Enhanced Photocatalytic Hydrogen Evolution Activity Driven by the Synergy Between Surface Vacancies and Cocatalysts: Surface Reaction Matters - Wenhui Yue; Ziwei Ye; Cong Liu; Zehong Xu; Lingzhi Wang; Xiaoming Cao; Hiromi Yamashita; Jinlong Zhang (Advanced Science, 2024)
Abstract The incorporation of defects and cocatalysts is known to be effective in improving photocatalytic activity, yet their coupled contribution to the photocatalytic hydrogen evolution process has not been well‐explored. In this study, We demonstrate that the incorporation of S vacancies and NiSe can contribute to the improvement of charge separation efficiency via the formation of a strong electric field within the bulk ZnIn2S4 (ZIS) and on its surface. More importantly, We also demonstrate that the synergy of S vacancies and NiSe benefits the overall hydrogen evolution activity by facilitating the H2O adsorption and dissociation process. This is particularly important for hydrogen evolution taking place under alkaline conditions where the proton concentration is low, allowing ZISv‐NiSe (containing abundant S vacancies) to outperform ZIS‐NiSe under alkaline conditions. In contrast, under acid conditions, since there are already sufficient amounts of protons available for reaction, the hydrogen evolution activity became governed by the hydrogen adsorption/desorption process rather than the H2O dissociation process. This leads to ZIS‐NiSe exhibiting higher activity than ZISv‐NiSe due to its more favorable hydrogen adsorption energy. The findings thus provide insights into how defect and cocatalyst modification strategies can be tailor‐made to improve hydrogen evolution activity under different pH conditions.